Solid-phase electrochemiluminescence immunosensing platform based on bipolar nanochannel array film for sensitive detection of carbohydrate antigen 125 - Lu, Shaolong; Wu, Jiayi; Luo, Tao; Liu, Junjie; Xi, Fengna; Zhang, Wenhao (Frontiers in Chemistry, 2024)
Development of simple solid-phase electrochemiluminescence (ECL) immunosensor with convenient fabrication for high-performance detection of tumor biomarkers is crucial. Herein, a solid-phase ECL immunoassay was constructed based on a bipolar silica nanochannel film (bp-SNA) modified electrode for highly sensitive detection of carbohydrate antigen 125 (CA 125). Inexpensive and readily available indium tin oxide (ITO) electrode was used as the supporting electrode for the growth of bp-SNA. bp-SNA consists of a bilayer SNA film with different functional groups and charge properties, including negatively charged inner layer SNA (n-SNA) and positively charged outer layer SNA (p-SNA). The nanochannels of bp-SNA were used for the immobilization of ECL emitter tris(bipyridine)ruthenium(II) (Ru(bpy)3 2+ ), while the outer surface was utilized for constructing the immunorecognition interface. Due to the dual electrostatic interaction composed of electrostatic attraction from n-SNA and electrostatic repulsion from p-SNA, Ru(bpy)3 2+ could be stably confined within bp-SNA, providing stable and high ECL signals to the modified electrode. After amino groups on the outer surface of bp-SNA were derivatized with aldehyde groups, recognition antibodies could be covalently immobilized, and an immunosensor was obtained after blocking nonspecific sites. When CA 125 binds to the antibodies on the recognition interface, the formed complex reduces the diffusion of the co-reactant tripropylamine (TPA) to the supporting electrode, decreasing the ECL signal. Based on this mechanism, the constructed immunosensor can achieve sensitive ECL detection of CA 125. The linear detection range is from 0.01 U/mL to 100 U/mL, with a detection limit of 4.7 mU/mL. CA 125 detection in serum is also achieved. The construction immunosensor has advantages including simple and convenient fabrication, high stability of the immobilized emitter, and high selectivity, making it suitable for CA 125 detection.